2015
DOI: 10.3390/ma8030914
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Low-Symmetry Structures from Phase Equilibrium of Fe-Al System—Microstructures and Mechanical Properties

Abstract: Fe-Al intermetallic alloys with aluminum content over 60 at% are in the area of the phase equilibrium diagram that is considerably less investigated in comparison to the high-symmetry Fe3Al and FeAl phases. Ambiguous crystallographic information and incoherent data referring to the phase equilibrium diagrams placed in a high-aluminum range have caused confusions and misinformation. Nowadays unequivocal material properties description of FeAl2, Fe2Al5 and FeAl3 intermetallic alloys is still incomplete. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 55 publications
(89 reference statements)
2
23
0
Order By: Relevance
“…Considering the iron-aluminium binary phase diagram, Alrich intermetallic compounds such as FeAl 2 , Fe 2 Al 5 , and Fe 4 Al 13 were reported to exhibit complex crystal structures, poor ductility, and low fracture toughness and consequently a brittle mechanical behaviour at low temperatures [19,20]. Though, cracks, oriented at a 45 ∘ angle to the sliding direction in the wear track and that propagate into a perpendicular orientation to the sliding direction, indicate brittle fracture of the Al-Si coating due to high tangential stresses at the sliding interface.…”
Section: Behaviour Of Al-si Coated 22mnb5mentioning
confidence: 99%
“…Considering the iron-aluminium binary phase diagram, Alrich intermetallic compounds such as FeAl 2 , Fe 2 Al 5 , and Fe 4 Al 13 were reported to exhibit complex crystal structures, poor ductility, and low fracture toughness and consequently a brittle mechanical behaviour at low temperatures [19,20]. Though, cracks, oriented at a 45 ∘ angle to the sliding direction in the wear track and that propagate into a perpendicular orientation to the sliding direction, indicate brittle fracture of the Al-Si coating due to high tangential stresses at the sliding interface.…”
Section: Behaviour Of Al-si Coated 22mnb5mentioning
confidence: 99%
“…Particularly noteworthy are the intermetallic Fe 3 Albased alloys that could potentially substitute for more expensive superalloys and creep-resistant steels. They are characterized by a combination of interesting functional characteristics such as an excellent resistance to oxidation, sulfidation and carburizing, good resistance to corrosion in sea water, high resistance to wear, erosion, or cavitation, and high strength to weight ratio [2][3][4][5][6]. The Fe 3 Al phase, depending on the chemical composition and temperature has either a D0 3 or B2 ordered structure, which is derivative of the body-centered cubic BCC or A2 structure.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was confirmed that the IC layers had very high values of Vickers hardness of about 549-714 HV. In addition, the Al-Fe ICs had high Vickers hardness values: 892 ± 6 HV, FeAl 2 ; 903 ± 7 HV, Fe 2 Al 5 ; and 691 ± 5 HV, FeAl 3 [26]. In other words, these microhardness measurements presented the possibility of IC creation by reaction between Al and SUS.…”
Section: Resultsmentioning
confidence: 81%